The Day a Woman Can Walk Freely on the Roads, That Day we Can Say that India Achieved Independence: Lessons to be Learned from Mahatma Gandhis Saying (Global Journal of Human-Social Science, 2015)
Nowadays, each and every state person, state, and other stakeholders in every country run to add something useful to its country. And in the twenty century an abrupt activity was fight for independence. Among the many India is the one. In such struggle, the mere dream/whim of freeing mother/father land from colonial and other kind of dominations was common in the world. By the time such fighters have already forgotten, and/or gave less emphasis to domestic issues though usually this action is not deliberate and well contemplated. Among the multifarious domestic issues the one and the most sensitizing was independence of women. And this kind of independence is the foundation and an indispensable tool to erect the nation/countrywide independence. Having disregarded such ideal means to change ones country to a better place someday, many has sustained failures and their struggle become full of ups and downs.
Keywords: independence; women's empowerment; freedom; and declaring independence